Electrical Conductivity Characteristic of TiO2 Nanowires from Hydrothermal Method - Rajan, Jose; Mohd Azlishah, Othman; Noor Faridah, Amat; Badrul Hisham, Ahmad (IOP Publishing, 2014)
One dimensional nanostructures of titanium dioxide (TiO2) were synthesized via hydrothermal method by mixing TiO2 as precursor in aqueous solution of NaOH as solvent. Then, heat and washing treatment was applied. Thus obtained wires had diameter ~15nm. TiO2 nanowires will be used as a network in solar cell such dye-sensitized solar cell in order to improve the performance of electron movement in the device. To improve the performance of electron movement, the characteristics of TiO2 nanowires have been analyses using field emission scanning electron microscopy (FESEM) analysis, x-ray diffractometer (XRD)analysis and brunauer emmett teller (BET) analysis. Finally, electrical conductivity of TiO2 nanowires was determined by measuring the resistance of the TiO2 nanowires paste on microscope glass.